Keefektifan Peer Support Untuk Meningkatkan Self Discipline Siswa SMP - Debora Primawati Widayat (JKI (Jurnal Konseling Indonesia), 2016)
Specifically, this research aims to present a picture of the effectiveness of peer support to increase self-discipline. The subject in this research is students of Junior High School 27 Malang that have low self discipline. The research instrument in this research is scale of self-discipline consists of 90 items, processed using time series design. The suggestions for this research is: 1) The counselor, the results and findings of this research can be used as information to help counselors to improve and develop services in schools; 2) For schools, this research can be expected to be used as information to improve students' self-discipline through the use of guidance and counseling services and peer support; 3) For students, peer support can be used to increase self discipline untill the students of Junior High School can achieve best development tasks; 4) Further researcher, this research data can be used as the material research to develop advanced research on a wider scope with regard to aspects of self-discipline. Keyword: Peer Support, Self Discipline, Students of Junior High School